O jogo que nunca acabou: a permanência do maracanaço no imaginário dos brasileiros e suas reatualizações contemporâneas - Corteze, Késia Costenaro (2015)
This study aims to relate two peculiar events that marked the history of Brazil in relation to football: The 1950 and 2014 World Cup. The only two events held in Brazil were characterized by great preparation of the event infrastructure and enormous expectations of the crowd by winning the title, but it was not what happened. The two Brazilian Cups have been characterized by two very significant losses, the Maracanaço and Mineiraço, these were compared by fans and media and regarded as the worst defeats of the Brazilian team. To understand this problematic we carried out a Virtual Ethnography in Twitter platform in order to verify what users were commenting on the particular subject, as well as research in newspaper archives available online to also observe how the media have related these two Brazilian losses Thus, it was possible to understand with Maracanaço (1950) was gaining new meanings and updated with the new Brazilian defeat in 2014, the Mineiraço.